2011
DOI: 10.1002/chem.201102026
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear–Dinuclear Equilibrium of Grafted Copper Complexes Confined in the Nanochannels of MCM‐41 Silica

Abstract: Following the structural concept of copper-containing proteins in which dinuclear copper centers are connected by hydroxide bridging ligands, a bidentate copper(II) complex has been incorporated into nano-confined MCM-41 silica by a multistep sequential grafting technique. Characterization by a combination of EPR spectroscopy, X-ray photoelectron spectroscopy (XPS), UV/Vis spectroscopy, IR spectroscopy , and solid-state (13)C and (29)Si cross-polarization magic-angle spinning (CP-MAS) NMR suggests that dinucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 84 publications
(146 reference statements)
3
22
0
Order By: Relevance
“…Elemental chemical analysis showed that the C/N molar ratio of 16.3 in the as-made sample is much less than that of 19.0 in surfactant molecule, which indicated that TPA + molecules were ion-exchanged into pore channel, in line with results in literatures [26,[42][43][44]. The TG-DTG analysis also showed that surfactant molecules and TPA molecules coexisted in the particles (Fig.…”
Section: Resultssupporting
confidence: 87%
“…Elemental chemical analysis showed that the C/N molar ratio of 16.3 in the as-made sample is much less than that of 19.0 in surfactant molecule, which indicated that TPA + molecules were ion-exchanged into pore channel, in line with results in literatures [26,[42][43][44]. The TG-DTG analysis also showed that surfactant molecules and TPA molecules coexisted in the particles (Fig.…”
Section: Resultssupporting
confidence: 87%
“…22,23,31,32,43,44 Mono (1:1) and bis (1:2) complexes have been noted, with monocomplexes favored at low surface coverage. 22,23,31,32,43,44 Formation of tris from bis complexes is not likely given that log K 3 = −1, 31,45 while log K 1 = ∼11 and log K 2 = ∼10.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…45 Several coordination environments are possible as depicted in Scheme 2, including (a) Cu 2+ coordinated to two ethylenediamine ligands to form a bis (1:2) complex; 32 (b) Cu 2+ coordinated to one ethylenediamine ligand to form a mono (1:1) complex with the other two sites filled with oxygen, possibly from silanol or Si−O−Si groups; 32 (c) Cu 2+ coordinated to four oxygens from silanol or Si−O−Si groups present on the surface; 32 or (d) dinuclear copper. 44 Option c can be discounted as the control experiments (i.e., films and gradients prepared without diamine or triamine chelating groups) showed no copper ( Figure 3D). …”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…To further prove the core role of surface ligands packing for tuning the PL of metal NCs, functional organosilanes with targeted carbonyl and amino groups in 3-(triethoxysilyl)propylsuccinic anhydride and aminopropyl triethoxysilane, respectively, were covalently grafted on mesoporous silica (Fig. 4a, b) [28][29][30] . It should be mentioned that the functional group in the targeted organosilane contains electron-rich heteroatoms, such as oxygen (O) and nitrogen (N) with unpaired lone electrons, as with protective templates for the synthesis of metal NCs, such as unconjugated polymers containing carboxylate groups, proteins and amino acid molecules with nitrogen (N), oxygen (O), sulfur (S), phosphorus (P), and others.…”
Section: Solvent-induced Ligand-dependent Emission Of Individual Aumentioning
confidence: 99%